Employee Adherence to a Tobacco-Free Executive Order in Kentucky. Issue 1 (January 2019) - Ickes, Melinda J.; Wiggins, Amanda; Rayens, Mary Kay; Edwards, Jean; Hahn, Ellen J.
Purpose: Examine predictors of short- and long-term adherence to a tobacco-free policy prohibiting all tobacco use inside and outdoors on Executive Branch property in Kentucky. Design: Cross-sectional online surveys administered at 2 time points. Setting: Commonwealth of Kentucky. Participants: 27 000 employees of the Kentucky Executive Branch were invited to participate in 2 online surveys: March 2015, 4 months postpolicy (N = 4854) and August 2015, 9 months postpolicy (N = 3522). Intervention: Executive order prohibiting tobacco use on Executive property implemented November 2014. Measures: Tobacco use, tobacco users' adherence to the tobacco-free policy, and personal characteristics were assessed. Analysis: Two separate logistic regression models used to determine predictors of short- and long-term adherence to the policy. Results: In the short term, employees who had seen others violate the policy ( P < .001) and had more tobacco-using friends ( P = .020) were less likely to adhere to the policy. At 9 months after the policy, employees who were older ( P = .038) and those who had seen others violate the policy ( P < .001) were less likely to report adherence to the policy. Tobacco-using employees who worked in a county with a comprehensive smoke-free ordinance ( P = .047) were more likely to adhere to the policy. Conclusion: This study indicates the need for strong policy compliance procedures, employer-based tobacco treatment programs accompanying tobacco-free policy change, and smoke-free workplace laws to promote prohealth norms.